Perguruan Tinggi Islam di Era Konversi IAIN ke UIN; Upaya Integritas kajian Ilmu Agama dan Umum - S Safrilsyah (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
The founding of Indonesia higher Islamic education (PTAI) isaimed to develop Islamic studies discourses and create intellectualulama and religious scientists. But, in the PTAI development as the frontline educational media for Islamic studies needs to make contact and dialog with other knowledge. Dichotomy between secular (non religious oriented knowledge) and religious oriented knowledge causes PTAI confined to develop its studies. That is also the tendency in the present time, in which Islamic studies seems to be irrelevant to modern life. This short article explains about the IAIN conversion process to UIN as integrating efforts of religious studies to that of secular knowledge which are based on the paradigm of hree knowledge: ontology, epistemology, and axiology/pragmatism. By applying these three paradigms all together, IAIN can ease the way to alleviate its status from IAIN to UIN. Integrating knowledge cannot be done by ignoring the paradigms. Because, a iscourse will remain secular if it is not based on ontological perspective or firm and complete world view or Tauhid (the Oneness principle). Also, an epistemology of knowledge will remain exploitative and abusive if it is not based on Islamic ontology. One should otice that the disintegrated construction of knowledge would be useless in the hand of immoral scholars. To do so, while doing conversion, axiological part should be constructed